Advances in Hydrology and Hydrogeology: Implications for Environmental Sustainability - Dr. Ghanshyam Shakar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
With an emphasis on their implications for environmental sustainability, this study examines the most recent developments in hydrology and hydrogeology. New advances in groundwater management, water cycle modeling, and hydrological data collection methods are revolutionizing our understanding of water resources in relation to urbanization and climate change. By combining cutting-edge technologies like machine learning, GIS, and remote sensing, we are improving our capacity to forecast patterns of water distribution, quality, and availability. These developments are also essential to sustainable water management techniques, such as effective irrigation, water conservation, and pollution prevention. The study also emphasizes how surface and groundwater systems are interdependent and how holistic methods are crucial for managing water resources. To address the escalating issues of water shortages, environmental degradation, and ecosystem preservation, the paper’s conclusion highlights the necessity of interdisciplinary cooperation and policy integration, eventually promoting long-term environmental sustainability.